IMPLEMENTASI PERATURAN MENTERI PENDIDIKAN NASIONAL RI NOMOR 27 TAHUN 2008 TENTANG STANDAR KUALIFIKASI AKADEMIK DAN KOMPETENSI KONSELOR DI SMA BHAKTI SUCI JAYA TANJUNG BATU KABUPATEN OGAN ILIR - evi sepriati; Qurniati Qurniati; Mud Dharminto; Eka Hoiriyah; Ellin Zahara (Jurnal Ilmu Administrasi dan Studi Kebijakan (JIASK), 2022)
The title of this research is "Implementation of the Regulation of the Minister of National Education of the Republic of Indonesia Number 27 of 2008 concerning Academic Qualification Standards and Counselor Competencies at Bhakti Suci Jaya High School Tanjung Batu, Ogan Ilir Regency". The formulation of the research problem is how to implement the Regulation of the Minister of National Education of the Republic of Indonesia Number 27 of 2008 concerning Academic Qualification Standards and Counselor Competencies at Bhakti Suci Jaya High School Tanjung Batu, Ogan Ilir Regency. With a qualitative research methodology, this study wanted to describe the implementation of the Regulation of the Minister of National Education of the Republic of Indonesia Number 27 of 2008 at SMA Bhakti Suci Jaya Tanjung Batu, based on data obtained from documentation, interviews, and observations. The results of the research are descriptive data on four factors of the public policy implementation model according to Edward, namely communication, resources, attitudes, and bureaucratic structure, which affect the implementation of the Regulation of the Minister of National Education of the Republic of Indonesia Number 27 of 2008 concerning Academic Qualification Standards and Counselor Competencies. Based on the results of this study, several things can be recommended, namely the need for sustainable structured communication and an attitude from the government that supports the achievement of qualification standards and counselor competencies so that the guidance and counseling program in schools is implemented.